Plasmid-free production of the plant lignan pinoresinol in growing Escherichia coli cells - U. Joost Luelf; Alexander Wassing; Lisa M. Böhmer; Vlada B. Urlacher (Microbial Cell Factories)
Abstract Background The high-value aryl tetralin lignan (+)-pinoresinol is the main precursor of many plant lignans including (-)-podophyllotoxin, which is used for the synthesis of chemotherapeutics. As (-)-podophyllotoxin is traditionally isolated from endangered and therefore limited natural sources, there is a particular need for biotechnological production. Recently, we developed a reconstituted biosynthetic pathway from (+)-pinoresinol to (-)-deoxypodophyllotoxin, the direct precursor of (-)-podophyllotoxin, in the recombinant host Escherichia coli. However, the use of the expensive substrate (+)-pinoresinol limits its application from the economic viewpoint. In addition, the simultaneous expression of multiple heterologous genes from different plasmids for a multi-enzyme cascade can be challenging and limits large-scale use. Results In this study, recombinant plasmid-free E. coli strains for the multi-step synthesis of pinoresinol from ferulic acid were constructed. To this end, a simple and versatile plasmid toolbox for CRISPR/Cas9-assisted chromosomal integration has been developed, which allows the easy transfer of genes from the pET vector series into the E. coli chromosome. Two versions of the developed toolbox enable the efficient integration of either one or two genes into intergenic high expression loci in both E. coli K-12 and B strains. After evaluation of this toolbox using the fluorescent reporter mCherry, genes from Petroselinum crispum and Zea mays for the synthesis of the monolignol coniferyl alcohol were integrated into different E. coli strains. The product titers achieved with plasmid-free E. coli W3110(T7) were comparable to those of the plasmid-based expression system. For the subsequent oxidative coupling of coniferyl alcohol to pinoresinol, a laccase from Corynebacterium glutamicum was selected. Testing of different culture media as well as optimization of gene copy number and copper availability for laccase activity resulted in the synthesis of 100 mg/L pinoresinol using growing E. coli cells. Conclusions For efficient and simple transfer of genes from pET vectors into the E. coli chromosome, an easy-to-handle molecular toolbox was developed and successfully tested on several E. coli strains. By combining heterologous and endogenous enzymes of the host, a plasmid-free recombinant E. coli growing cell system has been established that enables the synthesis of the key lignan pinoresinol.